Pola Komunikasi Interpersonal Orang Tua Terhadap Motivasi Belajar Anak Di Masa Pandemi Covid-19 - Sukmawati Putri , Iin; Zelfia, Zelfia; Rahmawati, Sitti (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This study aims to determine how parents' interpersonal communication patterns on children's learning motivation can be applied during the COVID-19 pandemic, both within the family and social interactions. This study uses qualitative research methods and is located in Makassar City, Tamalanrea Jaya Village, Tamalanrea District. Data collection is by using observation, interview, and documentation techniques as supporting materials in data collection. This research lasted for 1 month and as for the informants in this study amounted to 4 people The results showed that communication is a way to convey something to others in the form of ideas, facts, thoughts, and values. Communication between parents and children can provide motivation to learn so that it can improve children's learning achievement, but this cannot be separated from the role of teachers and parents who guide the learning process. Parents need to interact with children by communicating so that the relationship remains well established, that's why interaction is needed because it affects the relationship between parents and children, with the interaction of parents and children will be closer.